Monik Pro UMKM : Sebuah Inovasi Pelayanan Izin Usaha di DISKOPUKM Provinsi Sumatera Barat - Utami, Venaya Nurul; Helmi, Rahmadhona Fitri (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The low number of MSMEs in West Sumatra with legal business status hinders their competitiveness. This is due to distant licensing locations, complicated procedures and low awareness of the importance of legality. In order to overcome this problem, the West Sumatra Province Cooperative and UKM Office launched a business licensing innovation called Monik Pro UMKM. However, its implementation still faces challenges. Descriptive qualitatatibe method was used as research approach through interviews and documentation. The results of the study show that the Monik Pro UMKM innovation has been implemented quite well in accordance with Rogers’ innovation attribute theory. The supporting factors are leadership that supports innovation, employess who are educated and trained and the development team. While the inhibiting factors are internet netwotk and low public understanding of service technology.